Second‐generation antisense oligonucleotides against β‐catenin protect mice against diet‐induced hepatic steatosis and hepatic and peripheral insulin resistance. Issue 3 (7th December 2015) - Popov, Violeta B.; Jornayvaz, Francois R.; Akgul, Emin O.; Kanda, Shoichi; Jurczak, Michael J.; Zhang, Dongyan; Abudukadier, Abulizi; Majumdar, Sachin K.; Guigni, Blas; Petersen, Kitt Falk; Manchem, Vara Prasad; Bhanot, Sanjay; et al.
Abstract : Although mutations in the Wnt/β‐catenin signaling pathway are linked with the metabolic syndrome and type 2 diabetes in humans, the mechanism is unclear. High‐fat‐fed male C57BL/6 mice were treated for 4 wk with a 2'‐ O ‐methoxyethyl chimeric antisense oligonucleotide (ASO) to decrease hepatic and adipose expression of β‐catenin. β‐Catenin mRNA decreased by ã80% in the liver and by 70% in white adipose tissue relative to control ASO‐treated mice. β‐Catenin ASO improved hepatic insulin sensitivity and increased insulin‐stimulated whole body glucose metabolism, as assessed during hyperinsulinemiceuglycemic clamp in awake mice. β‐Catenin ASO altered hepatic lipid composition in high‐fat‐fed mice. There were reductions in hepatic triglyceride (44%, P < 0.05) and diacylglycerol content (60%, P < 0.01) but a 30% increase in ceramide content ( P < 0.001). The altered lipid content was attributed to decreased expression of sn ‐1, 2 diacylglycerol acyltransferase and mitochondrial acyl‐CoA:glycerol‐ sn ‐3‐phosphate acyltransferase and an increase in serine palmitoyl transferase. The decrease in cellular diacyglycerol was associated with a 33% decrease in PKCε activation ( P < 0.05) and 64% increase in Akt2 phosphorylation ( P < 0.05). In summary, Reducing β‐catenin expression decreases expression of enzymes involved in hepatic fatty acid esterification, ameliorates hepatic steatosis and lipid‐induced insulin resistance.—Popov, V. B., Jornayvaz, F. R., Akgul, E. O., Kanda, S., Jurczak, M. J., Zhang, D., Abudukadier, A., Majumdar, S. K., Guigni, B., Petersen, K. F., Manchem, V. P., Bhanot, S., Shulman, G. I., Samuel, V. T., Second‐generation antisense oligonucleotides against β‐catenin protect mice against diet‐induced hepatic steatosis and hepatic and peripheral insulin resistance. FASEB J. 30, 1207–1217 (2016). www.fasebj.org